Microstructure of ITO for Transparent Electrode on Glass Slide Prepare by RF Sputtering Technique - N Sangwaranatee; I Srithanachai; S Niemcharoen (My University, 2021)
Abstract Indium tin oxide (ITO) is an absorber photovoltaic material and widely used for semiconductor work for long time. ITO has characteristics by high transparent and low resistivity that can use for electrode of photodetector. Area of photodetector has use for metal contact but if change metal contact to transparent contact will get more photocurrent. However, this paper will investigate microstructure of ITO by analyze physical properties of material by various deposite time. The results show that transparent properties show around 97% at growth 1h and annealing at 500°C. XRD results show ITO peak (222), (400), (622) and (441) at sputtering time 60 mins.
Keywords: Photocurrent; Indium tin oxide; Industrial Vision Systems and Defect Detection